Low prevalence of gingival overgrowth associated to new imunossupressive protocols with cyclosporin - Luiz Augusto Wentz; Sara Cioccari Oliveira; Carlos Heitor Cunha Moreira; Cassiano Kuchenbecker Rösing (Sociedade Brasileira de Pesquisa Odontológica, 2012)
Gingival overgrowth (GO) is a frequent finding in patients treated with cyclosporine (CsA). This study investigated the prevalence and severity of GO in patients who received kidney transplant and CsA therapy, as well as associations with pharmacological and clinical factors. This cross-sectional study included 63 kidney transplant recipients who were treated with CsA in a university hospital. Demographic, pharmacological, and periodontal data were collected. The primary variable was GO. Independent sample t- and chi-square tests were used to compare means in groups with versusl without GO. The response rate was 86.3%. Overall, 40% of patients had some degree of GO. Eleven individuals presented GO scores > 10%, and 5 individuals reached 30%. The mean GO percentage was low (6.79 ± 15.83). Patients that were concurrently under nifedipine treatment showed a non-significant trend toward a greater prevalence of GO. Mean CsA dosage and serum levels were 3.20 ± 0.94 mg/kg/d and 156.12 ± 162.75 ng/mL, respectively. There were no statistically significant differences between patients with versusl without GO nor between the groups receiving nifedipine, no drug, or verapamil. The GO prevalence and severity rates were lower than those reported in previous studies and seemed to be independent of drug interactions.